Disordered eating in anorexia nervosa: give me heat, not just food - Gutierrez, Emilio; García, Naomi; Carrera, Olaia (Frontiers in Public Health, 2024)
The recommendation of applying external heat to patients with anorexia nervosa (AN) was first mentioned by William Gull in 1874, a procedure he learnt while acting as a consultant physician dispensing the medical certification required by wealthy clientele for admittance to Ticehurst asylum, one of the most successful and reputable private asylums in England. Gull attributed the original foundations of this practice to the studies of Charles Chossat (1796-1875), a physiologist, physician, and politician from Geneva, who discovered by chance the healing effects of heat on starved animals. In the 20th century, serendipity was once again to provide further evidence of the beneficial effect of heat on starved animals by underscoring the anomalies observed following a breakdown in the thermostats controlling the temperature of a laboratory. In the 21st century, experimental research has empirically substantiated the crucial role of ambient temperature (AT) in the animal model of Activity-Based Anorexia (ABA). Recent translational research has shown that a warmed environment reduced AN patients' anxiety around mealtime, a method more effective than exposure-based procedures. However, in the face of overwhelming evidence from both animal and patient studies, it is difficult to comprehend how the impact of providing a warm environment to AN patients, particularly around mealtimes, continues to be a neglected area of research